Tariffs, The Terms of Trade and Domestic Prices in a Monetary Economy: A Further Analysis - Anderson, Richard K.; Takayama, Akira (Review of Economic Studies, 1981)
Richard K. Anderson, Akira Takayama; Tariffs, The Terms of Trade and Domestic Prices in a Monetary Economy: A Further Analysis, The Review of Economic Stud